Epstemi's content of the philosophical and literary speeches in light of the challenges of The Times - Mansouri Maiz , Houria (Journal of Social Sciences and Humanities, 2023)
The research in the field of abstract of the speech remains among the first concerns that form the land of the cognitive and systematic content of the various speeches. The aim of our study is to highlight the importance of the concept of the approach in the analysis of speeches, particularly philosophical and literary speech. Recognizing the steps of the growth of the growth of the research in the various sciences, and include the conflict between theoretical perceptions and applied procedures, in order to remain a labor angle of special narrowness in the form of the complex and unique tensions of technical and technological development, Globalization and immunities of the "Episomics and Episodes" in various fields of thought, culture and the relevant interpretation plans. We can attach a non-exclusive list of questions that are long asked in the scientific field, and the media trading: Why do we care about the approach? How far can the developing curricula can be used in analysis and criticism of the "social phenomenon" in different letters? What means to interpret and understand the role of humanities of general, philosophy and literature in particular in the construction of the GND, what relations? What are the interactions and dialogues? How to live together despite our differences in a world less than the world of assumption, "he stresses that it is difficult to create on the ground. The cultural globalization of the stronger countries is entitled to a permanent confrontation with the preparations across the world's most beautiful? What is the progress made to humanity today and tomorrow? The rational use of the letter of the speech, which will strengthen the fate of the letters of the defense", "which will require consideration of the way of living and good measure. To achieve this goal, attention to the science of various disciplines through which the methods of ways and means of knowledge and science